Guest

∑cosA=∑sinA=0 then the value of X sin(2A-B-C) × X sin(2B-C-A) × X sin(2C-A-B)

∑cosA=∑sinA=0 then the value of Xsin(2A-B-C) × Xsin(2B-C-A) × Xsin(2C-A-B)

Grade:12

1 Answers

Yogendra Kumar
askIITians Faculty 122 Points
6 months ago
Hi, please repost your question by checking it once or if possible provide the clear image of the question.

Thank you

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free